THE EFFECT OF PENSION BENEFIT ON MILLENNIAL EMPLOYEES LOYALTY WITH PREFERENCE AND MOTIVATION AS MEDIATOR IN JAKARTA - Joko Purwanto, Tri; R. Sudiardhita, I Ketut; Rizan, Mohamad (Dinasti Publisher, 2021)
This study aims to determine and analyze the influence of Pension Benefit on millennial employees in Jakarta through preference and motivation as mediators. This research uses a qualitative and quantitative method using SEM Amos. The number of respondents were 262 that determined by purposive sampling technique. The result shows that: Pension Benefit has a significant positive effect to the employees loyalty; Pension Benefit has a significant positive effect to the employees preference; Pension Benefit has a significant positive effect to the employees motivation; employees preference has a significant positive effect to the employees loyalty; employees motivation has a significant positive effect to the employees loyalty; Pension Benefit hasn't a significant positive effect to the employees loyalty through employees preference; Pension Benefit hasn't a significant positive effect to the employees loyalty through employees motivation.